MENUJU DESA SEHAT HILINAMAZIHONO MELALUI GENCATA (GERAKAN CEGAH STUNTING) KECAMATAN O’O’U NIAS SELATAN TAHUN 2024 - Famea Satulo Dakhi; Aprilianus Ndruru; Rehati Ndruru; Lisda Putri Wati Telaumbanua; Ica Anjeli Daeli; Renungkan Gaho; Aloysius Boby Halawa; Rekalaila Demerni Halawa; Sesilia Nelsia Yeslina Duha; Vinsensius Sofunatola Buulolo; Animan Lature; Edar Sintasi Maduwu; Hinsam Irene Saputra Sarumaha; Yobestiman Ndruru; Walsyukurniat Zendrato (Universitas Nias Raya, 2024)
The aim of this community service is to implement the GENCATA Program (Movement to Prevent Stunting), which was initiated to raise awareness and knowledge among the community about stunting prevention through the empowerment of village community groups, intensive socialization regarding stunting, local food management, and waste management practices. This program involves the formation of a Sustainable Community Care Group for Stunting, educational programs about stunting, and intensive stunting awareness campaigns by stunting care groups. It also focuses on women's empowerment through balanced nutrition practices, healthy eating habits, and hygiene at home, along with the